ILRI research on zoonoses in the Asia-Pacific region - Gilbert, Jeffrey (2013)
In terms of a broader picture of zoonoses and their impact on poor livestock keepers ILRI undertook a review for the Department for International Development UK in 2012. Initial Asia-based ILRI projects on zoonoses focused on highly pathogenic avian influenza H5N1 and were located in Indonesia. Efficacy of HPAI vaccination research was USAID-funded – with Government of Indonesia and FAO as partners (2007-09) and the other Department for International Development (DfID/UKAID 2007-10) implemented in conjunction with Government, Royal Veterinary College (UK) and International Food Policy Research Institute (IFPRI) – focused more on institutional challenges, and included a livelihood analysis, evaluation of risk management and communication and advocacy. The most substantial project implemented by ILRI in the Asia Pacific region with a focus on zoonoses was the Ecosystem Approaches to the Better Management of Zoonotic Emerging Infectious Diseases in SE Asia (EcoZD) project supported by IDRC, Canada. The project recently completed after a 5½ year project cycle. The core objective was to build capacity among researchers and other key stakeholders to utilise an EcoHealth approach in tackling a priority zoonosis(-es). During the first phase researchers and institutions were identified to form multi-disciplinary (trans-disciplinary) teams. More than just a series of training, teams were required to design, implement and write up the research, with mentoring by ILRI scientists and additional external experts.